Problematika dan Tingkat Akses Keuangan pada UMKM : Sebuah Pintu Kinerja yang Lebih Baik - Shofi, Fadhoilus (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This research seeks to examine the Issues and Level of Financial Access for MSMEs in Pamekasan Regency. This research is a quantitative study. The sample was calculated using the Slovin formula. The result of the Slovin formula calculation yielded a sample of 135 MSME respondents in Pamekasan Regency for this study. The sampling technique used in this research was Proportional sampling. Because the average responses from respondents regarding financial access, as depicted by Location, Use of Services and Financial Facilities, and Information, are not good, it can be concluded that the level of Financial Access for MSMEs is poor. Factor Analysis also found that the order of factors from the worst to the best or from the smallest to the largest is the Information Factor, Financial Facilities Factor, Service Factor, and Location Factor, which represent the Financial Access.